Assessment of Upper Digestive Tract Visualization with Gastroscopy in Patients at Drs. H. Amri Tambunan Regional General Hospital 2020-2021 - Tambunan, Asri Ludin (Universitas Muhammadiyah Sumatera Utara, 2022)
Gastrointestinal diseases are one of the health problems included in the global burden of disease. Examination to see the mucosa and lumen of the upper digestive tract directly ranging from the oropharynx, esophagus, stomach to proximal duodenum using an endoscope device called Gastroscopy (Gastrointestinal Endoscopy (GIE)/Esophagogastrictroduodenoscopy (EGD)). The purpose of this study was to find out the characteristics of patients who conducted gastroscopic examinations at RSUD Drs. H. Amri Tambunan period 2020-2021. This study is a descriptive study that used cross sectional design and total sampling method which is as many as 510 patients who meet the criteria for inclusion of gastroscopy examination. The results of this study showed that gastroscopic examinations were most commonly performed in male patients (52.4%), with the most age range of 41 - 60 years (49.6%), the most indications are epigastric pain (28%), and the most gastroscopic examination results are gastritis (22%). Patients with complaints of epigastric pain are often found at the diagnosis of gastritis. Epigastric pain is the chief complaint of patients most in gastrointestinal diseases, especially the upper gastrointestinal tract. This corresponds to the gastric organ which is the location of the main lesion on the examination of gastroscopy.